P2Y(2) Nucleotide Receptor Upregulation and Activation Mediates Neurite Extension in IL-1β-treated Mouse Primary Cortical Neurons - Peterson, Troy S. (2013)
The proinflammatory cytokine interleukin-1β (IL-1β), whose levels are elevated in the brain in Alzheimer’s and other neurodegenerative diseases, has been shown to have both detrimental and beneficial effects on disease progression. In this paper, we demonstrate that incubation of mouse primary cortical neurons (mPCNs) with IL-1β increases the expression of the P2Y(2) nucleotide receptor (P2Y(2)R) and that activation of the upregulated receptor with UTP, a relatively selective agonist of the P2Y(2)R, increases neurite outgrowth. Consistent with the accepted role of cofilin in the regulation of neurite extension, results indicate that incubation of IL-1β-treated mPCNs with UTP increases the phosphorylation of cofilin, a response absent in PCNs isolated from P2Y(2)R(−/−) mice. Other findings indicate that function blocking anti-α(v)β(3/5) integrin antibodies prevent UTP-induced cofilin activation in IL-1β-treated mPCNs, suggesting that established P2Y(2)R/α(v)β(3/5) interactions that promote G(12)-dependent Rho activation lead to cofilin phosphorylation involved in neurite extension. Cofilin phosphorylation induced by UTP in IL-1β-treated mPCNs is also decreased by inhibitors of Ca(2+)/calmodulin-dependent protein kinase II (CaMKII), suggesting a role for P2Y(2)R-mediated and G(q)-dependent calcium mobilization in neurite outgrowth. Taken together, these studies indicate that upregulation of P2Y(2)Rs in mPCNs under proinflammatory conditions can promote cofilin-dependent neurite outgrowth, a neuroprotective response that may be a novel pharmacological target in the treatment of neurodegenerative diseases.